Pengaruh Ekspor Sektor Industri Pengolahan terhadap PDB, Tingkat Pengangguran dan Investasi Asing di Indonesia Periode 2000 – 2022 - Laksmana Putri, Calivi Kezia; Nasrudin, Nasrudin (Politeknik Statistika STIS, 2024)
The manufacturing industry is one of the sectors that has the largest contribution to Gross Domestic Product (GDP) in Indonesia which absorbs a lot of labor. However, in 2022 the GDP of the manufacturing industry and the Open Unemployment Rate (TPT) have not yet reached the RPJMN target, even though Foreign Investment continues to increase. One of the things that is thought to affect these conditions is export performance. This study aims to analyze the effect of processing exports on processing industry GDP, unemployment, and foreign investment simultaneously. The data used is Indonesian annual data for the period 2000-2022. This study uses a simultaneous equation model with the Two Stage Least Square (2SLS) estimation method. The results obtained are that exports have an influence on manufacturing GDP directly and simultaneously on the level of unemployment and foreign investment. Based on the simulation, it is estimated that the RPJMN target for unemployment rate and GDP of manufacturing industry can be achieved if the export of manufacturing industry can increase up to 25 percent of the average observation period